2018
DOI: 10.1097/shk.0000000000000975
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Plasma Nitrite, l-Arginine and Asymmetric Dimethylarginine With Morbidity and Mortality in Patients With Necrotizing Soft Tissue Infections

Abstract: Background:The nitric oxide system could play an important role in the pathophysiology related to necrotizing soft tissue infection (NSTI). Accordingly, we investigated the association between plasma nitrite level at admission and the presence of septic shock in patients with NSTI. We also evaluated the association between nitrite, asymmetric dimethylarginine (ADMA), l-arginine, l-arginine/ADMA ratio, and outcome.Methods:We analyzed plasma from 141 NSTI patients taken upon hospital admission. The severity of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
(50 reference statements)
0
8
0
1
Order By: Relevance
“…Previous reports have demonstrated high baseline nitrite and nitrate levels in patients with NSTI. 61 A theoretical explanation for the absence of a nitrite+nitrate response in our cohort could be that nitric oxide synthase systems were already highly expressed at baseline.…”
Section: Original Researchmentioning
confidence: 88%
“…Previous reports have demonstrated high baseline nitrite and nitrate levels in patients with NSTI. 61 A theoretical explanation for the absence of a nitrite+nitrate response in our cohort could be that nitric oxide synthase systems were already highly expressed at baseline.…”
Section: Original Researchmentioning
confidence: 88%
“…The development of rapid diagnostic tools for NSTI, such as levels of disease-associated biomarkers, to support clinical decisions could increase the accuracy of early diagnosis, leading to swifter surgical exploration and treatment only when clinically indicated. However, to date, there are only a few studies of molecular biomarkers in NSTIs (22,(28)(29)(30)(31)(32), and these are limited to analyses of only a few markers. The comprehensive multiplex analysis of 36 analytes conducted here revealed, as expected, a greater systemic inflammatory response in NSTI patients than in noninfected patients (surgical controls).…”
Section: Discussionmentioning
confidence: 99%
“…The pathological activities of ADMA are particularly relevant to sepsis. Multiple studies have shown that high concentrations of ADMA are present in the blood of sepsis patients [26][27][28][29][30][31][32][33][34]. More importantly, ADMA levels in patients with sepsis correlate with disease severity (higher in septic shock) and mortality [26,30,33].…”
Section: Adma Levels and Sepsis Mortalitymentioning
confidence: 99%